2014
DOI: 10.3389/fpls.2014.00285
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide-independent generation of superoxide by plant peroxidase: hypotheses and supportive data employing ferrous ion as a model stimulus

Abstract: When plants are threaten by microbial attacks or treated with elicitors, alkalization of extracellular space is often induced and thus pH-dependent extracellular peroxidase-mediated oxidative burst reportedly takes place, especially at the site of microbial challenge. However, direct stimulus involved in activation of peroxidase-catalyzed oxidative burst has not been identified to date. Here, we would like to propose a likely role for free ferrous ion in reduction of ferric native peroxidase into ferrous enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 38 publications
(79 reference statements)
2
24
0
Order By: Relevance
“…19 We can expect that SA may interact with native form of plant peroxidases. In fact, such preliminary data on the SA-dependent stimulation of native HRP 21 and SBP 32 leading to generation of O 2 ¡ have been shown in our previous articles. However, when we have reported such data, it was early for us to clarify our working hypothesis on the mode of SA action in the H 2 O 2 -independent peroxidase action leading to generation of ROS.…”
Section: Proposed Modelmentioning
confidence: 92%
See 3 more Smart Citations
“…19 We can expect that SA may interact with native form of plant peroxidases. In fact, such preliminary data on the SA-dependent stimulation of native HRP 21 and SBP 32 leading to generation of O 2 ¡ have been shown in our previous articles. However, when we have reported such data, it was early for us to clarify our working hypothesis on the mode of SA action in the H 2 O 2 -independent peroxidase action leading to generation of ROS.…”
Section: Proposed Modelmentioning
confidence: 92%
“…However, when we have reported such data, it was early for us to clarify our working hypothesis on the mode of SA action in the H 2 O 2 -independent peroxidase action leading to generation of ROS. After publication of recent work by Kimura et al, 21 we examined and confirmed that SA actually induces the generation of O 2 ¡ in the presence of model enzymes such as HRP and SBP, even in the absence of H 2 O 2 supplementation. Here, typical data obtained with SBP are shown (Fig.…”
Section: Proposed Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently reported a likely mechanism involving free ferrous ion (Fe 2C ) in reduction of ferric native enzyme of purified HRP into ferrous enzyme intermediate which readily produces O 2 ¡ via formation of Compound III, especially under alkaline condition, thus, possibly contributing to the plant defense mechanism associated with pH changes. 18 Here, we report on the spectroscopic and CL evidences in support of the model for soybean POX (SBP)-catalyzed robust production of O 2 ¡ to be stimulated in the absence of conventional POX substrates but in the presence of free Fe 2C .…”
Section: Introductionmentioning
confidence: 99%